Decision Points: The Factors Influencing the Decision to Feed in the Medicinal Leech - Gaudry, Quentin; Kristan, William B. (Frontiers in Neuroscience, 2012)
The decision to feed is a complex task that requires several small independent choices. Am I hungry? Where do I look for food? Is there something better I’d rather be doing? When should I stop? With all of these questions, it is no wonder that decisions about feeding depend on several sensory modalities and that the influences of these sensory systems would be evident throughout the nervous system. The leech is uniquely well suited for studying these complicated questions due to its relatively simple nervous system, its exceptionally well-characterized behaviors and neural circuits, and the ease with which one can perform semi-intact preparations to study the link between physiology and decision-making. We will begin this review by discussing the cellular substrates that govern the decision to initiate and to terminate a bout of feeding. We will then discuss how feeding temporarily blocks competing behaviors from being expressed while the animal continues to feed. Then we will review what is currently known about how feeding affects long-term behavioral choices of the leech. Finally, we conclude with a short discussion of the advantages of the leech’s decision-making circuit’s design and how this design might be applicable to all decision circuits.